INTEGRASI DAN PERGERAKAN PRODUKSI, HARGA KARET (HEVEA BRASILIENSIS) DI KABUPATEN OGAN KOMERING ULU (JASEP, 2016)
This research aimed to analyze the level of integration and movement of Production and Rubber Price (Hevea brasiliensis) in District Ogan Komering Ulu. This Research was conducted in Ogan Komering Ulu. The research method used is book study method. The author uses secondary data obtained from the Department of Forestry and Plantations Ogan Komering Ulu, the Central Bureau of Statistics Ogan Komering Ulu and other agencies associated with this research. Then data is processed by views analysis tools version 7. Based on the results in the conclution that there is the integration of production and the price of rubber in Ogan Komering Ulu with weak levels of integration. This means that if there is a change in the production of rubber in Ogan Komering Ulu will not really affect the price of rubber in Ogan Komering Ulu with a very small changes, as well as the rubber price movements in the short term. Rubber price movementto make adjustments faster compare to the movement of the rubber production in Ogan Komering Ulu.